Impact of the COVID-19 pandemic on routine immunization coverage of children under 2 years in Asia: a systematic review - Robbiatul Afda'tiyah; Wiku Bakti Bawono Adisasmito; Fajaria Nurcandra (Jurnal Kesehatan Ibu dan Anak, 2022)
The COVID-19 pandemic has caused a disruption in essential health services which also has an impact on reducing the coverage of routine immunizations for children. A decrease in immunization coverage will increase the incidence of vaccine-preventable diseases. This study aimed to determine the coverage of routine immunization in children under 2 years of age during the COVID-19 pandemic in Asia. A systematic search was conducted to find relevant studies using keywords in 3 databases like Scopus, PubMed, and EMBASE, on October 24, 2022. The article's identification used the PRISMA method. Articles used were limited to 2020-2022. The reduction in immunization coverage or delays in immunization in children ranges from 16-71%. The most decrease in immunization coverage occurred in March-April 2020. Immunization coverage increased again in May 2020 and decreased back in September-October 2020. An overview of the decline in immunization is an evidence base for policy practitioners to carry out mitigation immediately. Continuation of the immunization program is very important for children's health and must remain a priority despite the ongoing pandemic.